Assessing the Inter-Rater and Inter-Trial Reliability of the NeurOptics Pupillary Light Response-3000 Pupillometer - Deborah A Jehu; Lori A Bolgla; Samantha Armas; Forest Dutton (International Journal of Sports Physical Therapy)
# Background